Punishment of Children as Perpetrators of Maltreatment Based on Restorative Justice - Afifah Suwandi , Chika; Fitriciada Azhari , Aidul (Journal of Law, Politic and Humanities, 2024)
The purpose of this study is to examine and analyze the application of criminal sanctions against children as perpetrators of restorative justice-based persecution in Semarang District Court Decision Number 5/Pid.Sus/Anak/2018/PN Smg. The method of approach in this writing is normative juridical. The specification of this research uses analytical descriptive. The data source uses secondary data. Data collection techniques using document studies. To analyze the data, researchers used qualitative analysis methods. The judge in deciding the case of maltreatment committed by a child against a child resulting in serious injury with a restorative justice approach in the Semarang District Court Decision Number 5/Pid.Sus/Anak/ 2018/PN Smg which states that the Defendant ARNES POLINUS SILALAHI alias ARPOL BIN J. SILALAHI is legally and convincingly proven guilty of committing the crime of "Participating in violence against children resulting in injury" as regulated and punishable in Article 80 paragraph (2) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection is correct. This is in accordance with the charges of the Public Prosecutor and has been based on the facts in the trial, as well as the evidence submitted by the Public Prosecutor in the form of testimony from witnesses that are in accordance with the results of the Visum Et Repertum. And the defendant is considered physically and mentally healthy so that he is considered capable of taking responsibility for his actions. In addition, the legal considerations of the Judge in imposing punishment against the defendant of the crime of violence against children which resulted in serious injury were also appropriate. The judge sentenced the defendant ARNES POLINUS SILALAHI alias ARPOL BIN J. SILALAHI to 5 (five) months imprisonment. The judge has considered both from a juridical point of view, the facts in the trial, the testimony of witnesses, existing evidence, and based on the conviction of the judge.